Mcm8 and Mcm9 form a dimeric complex in Xenopus laevis egg extract that is not essential for DNA replication initiation - Gambus, Agnieszka (Landes Bioscience, 2013)
Hexameric complexes of the six related Mcm2–7 proteins form the core of the replicative helicase. Two other proteins, Mcm8 and Mcm9, with significant homology to Mcm2–7 were first shown to play distinct roles during DNA replication in Xenopus laevis egg extract. Recent work has revealed that Mcm8 and 9 form a complex that plays a role during homologous recombination in human, chicken and mouse cells. We have therefore re-examined the behavior of the Xenopus homologs of these proteins. We show that Mcm8 and Mcm9 form a dimeric complex in Xenopus egg extract. They both associate with chromatin at later stages of DNA replication, and this association is stimulated by DNA damage, suggesting that their function is analogous to the one described in higher eukaryotes. In contrast to previous reports, we do not find Mcm9 essential for loading of Mcm2–7 complex onto chromatin during origin licensing nor detect its interaction with Cdt1 origin licensing factor. Altogether, we conclude that the role Mcm8 and Mcm9 play in Xenopus egg extract is not different from recent findings in higher eukaryotes, consistent with an evolutionary conservation of their function.